OPTIMALISASI DIGITAL SMART SOLUTION DALAM PEMASARAN PRODUK UMKM MAKARONI PADA MASA PPKM LEVEL IV DI KELURAHAN KUPANG KOTA KECAMATAN TELUK BETUNG UTARA - Ayu Firdhayanti; Nurjoko Nurjoko (JURNAL PENGABDIAN MANDIRI, 2022)
The rapid development of technology in the digital world and the internet of course also has an impact on the world of marketing. Digital marketing is more prospective because it allows potential customers to obtain all kinds of information about products and transact via the internet. Macaroni sales so far require consumers who want to order or buy products to come directly to the location or order via WhatsApp to see the products to be purchased. The purpose of this activity is to provide training and assistance to Macaroni SMEs regarding the implementation of Digital Smart Solutions as a strategy in marketing products. The training and mentoring phase consists of several activities, namely: (1) Introduction to packaging and branding, (2) Product documentation, (3) Introduction to social media, (4) Introduction to marketplaces, (5) Receiving orders and sending goods. The results of Community Service are Macaroni SMEs have social media and marketplaces as tools to promote products and Macaroni SMEs owners have an understanding of Digital Marketing and are able to manage their social media and marketplaces.